2004
DOI: 10.1038/sj.mp.4001558
|View full text |Cite|
|
Sign up to set email alerts
|

Schizophrenia genes, gene expression, and neuropathology: on the matter of their convergence

Abstract: This review critically summarizes the neuropathology and genetics of schizophrenia, the relationship between them, and speculates on their functional convergence. The morphological correlates of schizophrenia are subtle, and range from a slight reduction in brain size to localized alterations in the morphology and molecular composition of specific neuronal, synaptic, and glial populations in the hippocampus, dorsolateral prefrontal cortex, and dorsal thalamus. These findings have fostered the view of schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
1,363
8
27

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,837 publications
(1,435 citation statements)
references
References 393 publications
(444 reference statements)
37
1,363
8
27
Order By: Relevance
“…This developmental pattern is in accordance with the available data that early and transient disruptions in the developmental programs during brain development can produce a behavioral disease that manifests in adulthood. 6,61 Inducible expression of mutant hDISC1 in forebrain region resulted in a number of behaviors that have been associated with schizophrenia. 1,2,62 Intriguingly, the behavioral effects of mutant hDISC1 were sex dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This developmental pattern is in accordance with the available data that early and transient disruptions in the developmental programs during brain development can produce a behavioral disease that manifests in adulthood. 6,61 Inducible expression of mutant hDISC1 in forebrain region resulted in a number of behaviors that have been associated with schizophrenia. 1,2,62 Intriguingly, the behavioral effects of mutant hDISC1 were sex dependent.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Numerous genetic linkage and association studies have identified regions of the genome that may harbor schizophrenia risk genes, but the complex genetics and symptomatology of the disease have impeded efforts to identify clear genetic determinants. 5,6 An alternative approach is to study families in which schizophrenia and allied psychiatric disorders segregate with cytogenetic abnormalities. 7 In these families, a single major genetic defect could confer susceptibility to psychiatric illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…tions ( Figure 5b; F (1,14) = 5.7, P < 0.05) with KOSH animals showing a significant reduction in [ 3 H]pirenzepine binding in comparison to WTSH (P < 0.05).…”
Section: W T S H K O S H W T E E K O E E W T S H K O S H W T E E K O E Ementioning
confidence: 93%
“…These and other findings suggest that this brain disorder arises from a genetic predisposition affecting neurodevelopmental processes, combined with exposure to environmental risk factors. 14 The complexity of the underlying physiological basis is highlighted by the multitude of pathways that have been implicated in pathogenesis including those involving dopaminergic, 15,16 serotonergic, 17,18 muscarinic [19][20][21][22] and glutamatergic signaling pathways. [23][24][25] It is, therefore, significant that PLC-b1 represents a point of convergence for these signaling pathways and that levels of the protein have been shown to be altered in the cortex of chronic schizophrenic patients, increasing in the prefrontal cortex and decreasing in the superior temporal gyrus.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the paucity of dopamine transporters in prefrontal cortex (PFC), 6 COMT is a critical determinant of prefrontal dopamine flux. 7 The gene is located at 22q11.2, a region implicated in schizophrenia by linkage 8 and by the 22q11.2 syndrome (MIM#192430), a hemideletion associated with strongly increased risk of schizophrenia-like illness. 9 A common val 108/158 met substitution affects the stability of the protein and leads to a significant decrease in the activity of the enzyme in brain and lymphocytes.…”
Section: Introductionmentioning
confidence: 99%